수능 비문학 텍스트에 대한 학습자 인식 연구 - 강다연; Kang Dayeon; 김명순; Kim Myungsoon (독서연구, 2024)
목적: 수능 비문학 텍스트에 대한 학습자들의 인식을 살펴 비문학 텍스트에 지문 제시의 개선 방향을 모색한다. 방법: 부산·경남 소재 5명의 학생을 대상으로 실시한 두 차례의 면담을 바탕으로, 비문학 텍스트와 관련된 학습자의 경험과 요구를 분석한다. 결과: 비문학 텍스트를 읽을 때의 감정 반응은 긍정형(안도형, 흥미형, 안정형)과 부정형(공포형, 불안형, 회의형, 거부형), 무반응(적응형)으로 나타난다. 비문학 텍스트 독해를 저해하는 요인으로는 텍스트의 길이, 생소한 어휘, 시험 상황, 배경지식 부족, 과다한 정보량, 개인적 흥미 여부 등이 꼽힌다. 한편, 비문학 텍스트에 대한 평가는 텍스트 난도의 적절성 및 독서 능력 증진 여부 등에 따라 긍정 평가와 부정 평가로 나뉜다. 학습자들이 희망하는 관련 국어과 활동은 독해 능력 향상을 목적으로 한 경우와 수능을 목적으로 한 경우로 나뉘는데 전자는 중요도 구분 및 읽기 과정 점검, 후자는 기출문제 풀이 및 관련 배경지식 습득 등이 제시된다. 결론: 첫째, 비문학 텍스트에 대한 학습자들의 부정적인 감정 반응을 해소해야 한다. 둘째, 비문학 텍스트의 난도 조정이 필요하다. 셋째, 비문학 텍스트의 소재 및 내용을 검토해야 한다. Purpose: to investigate learners’ perceptions of non-literary texts in CSAT, the factors and demands for perceived difficulty, and to seek directions to improve non-literary texts. Methods: achieve the study’s goal, two interviews with four high school students and one dropout in Busan and Gyeongnam were conducted to examine the learners’ experiences, evaluations, and demands regarding nonliterary texts. Results: Learners’ perceptions of non-literary texts were as follows: ① Emotional responses when reading non-literary texts were positive (relief, interest, and stability), negative (fear, instability, skepticism, and rejection), and non-responsive (adaptive). ② Factors that hinder reading non-literary texts include the length of texts, unfamiliar vocabulary, test situations, lack of background knowledge, abundance of information, and personal interest. Non-literary texts are evaluated as either positive or negative, based on their difficulty and whether their reading ability has improved . Learning activities desired by learners were divided into cases aimed at improving reading ability and cases aimed at the CSAT. Conclusion: To discuss ways to improve nonliterary texts, learners’ negative emotional reactions to nonliterary texts must first be resolved. Second, the complexity of non-literary texts must be regulated. Third, the materials and contents of non-literary texts must be reviewed.